Helping the down and out rise again - Sunday, Mail (Star Publications (M) Bhd, 2015)
While most people celebrate their birthday with loved ones, Nasaruddin Jaafar spent his 30th birthday on Thursday walking the streets distributing food and firstaid items to homeless individuals.